Limitations in controlling white mold on common beans with Trichoderma spp. at the fall-winter season Limitações do controle do mofo-branco do feijoeiro com Trichoderma spp. no cultivo de outono-inverno - Trazilbo José de Paula Júnior (Summa Phytopathologica, 2012)
We studied the effectiveness of application of Trichoderma spp. in controlling white mold on common beans at the fall-winter crop in the Zona da Mata region of the State of Minas Gerais, Brazil. There was no effect of the antagonist in reducing the disease severity, which could be explained by the low temperatures and the high inoculum pressure in the field. We concluded that Trichoderma applications are not recommended for control of white mold on common beans at the fall-winter season in regions with average temperature bellow 20 °C, since this condition favor more the pathogen than the antagonist. Estudou-se a eficácia da aplicação de Trichoderma spp. no controle do mofo-branco do feijoeiro cultivado no outono-inverno na Zona da Mata de Minas Gerais. Não houve efeito do antagonista em reduzir a severidade da doença, o que pode ser explicado pelas baixas temperaturas e pela alta pressão de inóculo no campo. Conclui-se que aplicações de Trichoderma não são recomendadas para o controle do mofo-branco do feijoeiro no outono-inverno em regiões com temperatura média abaixo de 20 °C, considerando que essa condição climática favorece mais o desenvolvimento do patógeno do que o do antagonista.